The Early Diabetes Intervention Program – is early actually late?. Issue 8 (November 2014) - Bergman, Michael
Abstract This Commentary briefly reviews the background of prediabetes including its definition and pathophysiology and describes as well the natural course of glycemic deterioration as it follows a continuum. Research efforts in identifying glucose and other biomarkers for the early detection of high‐risk individuals are summarized.